ANALISIS PENGARUH KUALITAS SISTEM INFORMASI AKADEMIK TERHADAP KEPUASAN END-USER - Evi Yulianti (UNIVERSITAS INDO GLOBAL MANDIRI)
This study examined whether the five instruments developed by Doll and Torkzadeh from previous studies that include (contents, accuracy, format, user convenience, timeliness). Of the five instruments, whether the quality of academic information systems have an influence on the End-User satisfaction. And the factors which indicators of quality information system of Academic most influence on the End-User satisfaction in using the System Academic information. Data taken from the population of students as stakeholders of the most widely used academic information system and the number of samples selected were 303 people from 1246 students active in PTS. XYZ. The collection of data with direct surveys and disseminate questioner. The results showed that the independent variables consist of the content, accuracy, ease of use, and timeliness, individually significantly influence the dependent variable (Y). While the format of the individual variables had no significant effect on variable Y that is user satisfaction SIA. Key words: User Satisfaction Information, Academic